2012
DOI: 10.1111/j.1365-294x.2012.05580.x
|View full text |Cite
|
Sign up to set email alerts
|

Widespread yet heterogeneous genomic divergence

Abstract: Genetic differentiation during adaptive divergence and speciation is heterogeneous among genomic regions. Some regions can be highly differentiated between populations, for example, because they harbour genes under divergent selection or those causing reproductive isolation and thus are resistant to gene flow. Other regions might be homogenized by gene flow and thus weakly differentiated. Debates persist about the number of differentiated regions expected under divergence with gene flow, and their causes, size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 23 publications
4
39
0
Order By: Relevance
“…It is important to note that there are some examples of divergence with gene flow, where regions of the genome have reduced recombination rates due to adaptive genes being trapped in inversions (Noor et al 2001;Rieseberg 2001) or divergent selection reducing the flow of genomic regions containing adaptive genes, relative to neutral regions (Nosil and Feder 2012;Via 2012). However it is generally recognized that gene flow is an antagonistic force in the process of divergence Felsenstein 1981), with the biological species concept defining species based on presence or absence of interbreeding between groups (Mayr 1942).…”
Section: Reproductive Isolationmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to note that there are some examples of divergence with gene flow, where regions of the genome have reduced recombination rates due to adaptive genes being trapped in inversions (Noor et al 2001;Rieseberg 2001) or divergent selection reducing the flow of genomic regions containing adaptive genes, relative to neutral regions (Nosil and Feder 2012;Via 2012). However it is generally recognized that gene flow is an antagonistic force in the process of divergence Felsenstein 1981), with the biological species concept defining species based on presence or absence of interbreeding between groups (Mayr 1942).…”
Section: Reproductive Isolationmentioning
confidence: 99%
“…This model of speciation is dependent on divergent natural selection between contrasting environments as a primary cause of cessation of gene exchange Nosil 2012), as potentially interbreeding populations are driven toward contrasting adaptive peaks, leading to phenotypic divergence. Reproductive isolation arises when hybrids formed between the divergent populations have intermediate phenotypes and suffer fitness costs as a result, or selection can exclude immigrants based on phenotype environment mismatches.…”
Section: Ecological Speciationmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in speciation and hybridization genomics revealed that levels of genetic differentiation between species can be highly variable across the genome: genetic differentiation accumulates in certain genomic regions, while divergence is hampered in other regions by homogenizing gene flow, resulting in a heterogeneous genomic landscape (Nosil et al, 2009, Nosil and Feder, 2012b, Harrison and Larson, 2016. A consequence of this heterogeneity is that genomes are mosaics of different gene histories (Ellegren et al, 2012, Maddison, 1997, Payseur, 2010) that can be compared to unravel complex speciation and hybridization events (Ottenburghs et al, 2016a, Harrison andLarson, 2014).…”
Section: Reinforcement Speciation Reversal Hybrid Speciation Stable Hmentioning
confidence: 99%